2007
DOI: 10.1016/j.ijgo.2007.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Implications of incorrect determination of fetal sex by ultrasound

Abstract: Incorrect determination of fetal sex by ultrasound has implications that can affect the mental and psychological health of the mother and the upbringing of the newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 9 publications
0
26
1
Order By: Relevance
“…In 1994, India passed a law prohibiting doctors and clinics from determining the sex of the fetus using diagnostic techniques due to traditional primogeniture [11]. A study conducted in Nigeria has also found that incorrect sex determination through ultrasound has led to domestic violence and marital conflicts [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1994, India passed a law prohibiting doctors and clinics from determining the sex of the fetus using diagnostic techniques due to traditional primogeniture [11]. A study conducted in Nigeria has also found that incorrect sex determination through ultrasound has led to domestic violence and marital conflicts [3].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, computer vision could compare images obtained during an exam to a control set of images to detect possible complications and present the image that possibly contains a complication to the midwife to verify the possible condition exists. Finally, it could be beneficial to use computer vision to obscure the gender of the fetus, potentially avoiding problems observed elsewhere [3,11,16].…”
Section: Future Workmentioning
confidence: 99%
“…The presence of private ultrasound facilities couple with the fact that people pay for services out of pocket means that women can perform self referrals for ultrasound examinations for as many times as they can afford leading to overuse of the service. Chigbu et al 19 working in Nigeria have shown the serious social and psychologic implications in the wrong assignment of fetal sex. This abuse calls for strict guidelines for sonographers practicing in developing countries.…”
Section: Dangers Of Obstetric Ultrasound Scanning In Developing Countmentioning
confidence: 99%
“…Such use of ultrasonography not only has implications for abortion rates and sex ratios, but also carries the potential consequences of incorrect assessment. In a Nigerian study [23], some women who delivered a female neonate after being told that their fetus was male via ultrasonography reported negative experiences such as marital conflict (including physical violence from their partners) and regret toward tubal ligation. A Ghanaian study [24] showed an ultrasonography accuracy of only 86.5% for detection of fetal sex.…”
Section: Discussionmentioning
confidence: 99%